Interpersonal Communication to Teenagers in Purwokerto, Indonesia - Twi Lia Widiyawati; Dyah Astorini Wulandari (Proceedings Series on Social Sciences & Humanities, 2021)
Interpersonal communication is communication made by two or more people that produces a response both verbally and nonverbally. This study aims to describe the interpersonal communication possessed by adolescents in Purwokerto. The participants in this study were active teenagers from one of the private junior high schools in Purwokerto (n = 47). The research method used in this study is a quantitative descriptive approach with data collection using the Interpersonal Communication scale and measured using aspects of interpersonal communication Devito (2013), namely: openness, Empathy, supportive attitude, positive attitude, and equality. From the results of the research they have conducted. This shows the level of interpersonal communication in students, with the result that 24 students or 51.7% of students in Purwokerto have difficulty or difficulty in communicating. In comparison, 23 students, or 48.3% of students in Purwokerto, have no problem communicating interpersonally. Based on these results, it is expected that educational institutions can explore and provide more stimulus to improve interpersonal communication to students.